The Effect of Transformational Leadership, Career Adaptation, and Career Commitment on Lecturer Career Success the Role of Job Embeddedness at La Tansa Mashiro College Banten - Wildan Wildan; Hamidah Hamidah; Dewi Susita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Based on career construction theory and job attachment theory, the aim of this study is to provide insight into the interaction between transformational leadership, career adaptation, and career commitment on career success and the role of job embeddedness as moderating. A quantitative approach is used for this research. Data were collected from 129 lecturers at La Tansa Mashiro College. Rangkasbitung, Banten. Hypothesis testing using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the effect of transformational leadership on career adaptation is not significant, job embeddedness as a moderator is needed for lecturer career success.